2020
DOI: 10.21037/tcr-20-1294
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: potential biomarkers for diagnosis and prognosis of different cancers

Abstract: A thorough understanding of the tumor environment and underlying genetic factors helps in the better formulation of cancer management strategies. Availability of efficient diagnostic and prognostic biomarkers facilitates early detection and progression of the disease. MicroRNAs affect different biological processes participating in tumorigenesis through regulation of their target genes. An expanding list of unique RNAs and understanding of their regulatory role has opened up a new field in cancer research.Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 218 publications
(330 reference statements)
0
21
0
2
Order By: Relevance
“…The outcomes of various researches have shown that many miRNAs have a positive value for gastric cancer in prognosis [ 22 , 36 ]. Recent progress in prognosis and treatment has considerably increased the long-term survival for patients with early gastric cancer [ 10 ]. For instance, downregulation of miR-451 was associated with worse prognosis of gastric cancer patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of various researches have shown that many miRNAs have a positive value for gastric cancer in prognosis [ 22 , 36 ]. Recent progress in prognosis and treatment has considerably increased the long-term survival for patients with early gastric cancer [ 10 ]. For instance, downregulation of miR-451 was associated with worse prognosis of gastric cancer patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in tumor cells, the dysregulation of microRNAs (abbreviated as miRNAs or miRs), as an abundant class of endogenous noncoding RNAs (about 18∼24 nt) suggests their tumorigenic or antitumorigenic effects on target genes expressed in the tumor environment [ 9 , 10 ]. Several miRNAs were showed to be related to the development and progression of gastric cancer, which also could predict the status of LNM before the surgical operation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…miRNAs play important roles in several biological processes, including organ development, cell proliferation, apoptosis, and differentiation [ 7 , 8 , 9 , 10 ]. As their targets include oncogenes and/or tumor suppressor genes, miRNAs can function as tumor promoters or suppressors, and, due to their tissue- and disease-specific expression, they are often ideal candidates as tumor biomarkers [ 11 ]. Furthermore, miRNAs may confer specific features to tumors, including resistance to radiation and chemotherapy, cancer stem cell (CSC) maintenance as well as augmented angiogenesis [ 12 ], therefore constituting prognostic markers and/or therapeutic targets [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%